Attitudes of University of the Philippines entering freshmen students towards physical education - Buendia, Lydia (Evangelista) 1929- (s.n.], 1967)
A reliable and valid measure of the individual and group attitudes toward physical education is made in this study. Specifically, a scale measure is constructed to measure the attitudes of entering freshman students of the University of the Philippines toward physical education in order to determine if these attitudes are favorable or not. The physical education activity preferences of the same students are also determined.